Cyclodextrin-Based Metal-Organic Framework as an Application Platform for Bioactive Ruthenium(III) Complexes - Marzabad, Mahya Asgharian; Kollárová, Sára; Pan, Fangfang; Novák, Martin; Kuta, Jan; Rissanen, Kari; Babica, Pavel; Marek, Radek; Jurček, Ondřej (Inorganic chemistry, 2025)
Ruthenium(III) complexes are promising anticancer metallodrugs because of their antimetastatic (migrastatic) potential and significantly lower host toxicity than generally used platinum metallodrugs. On the other hand, the ruthenium(III) complexes generally show low solubility and stability in an aqueous environment but exhibit some toxicity associated with unspecific delivery. For these reasons, numerous ongoing studies deal with their encapsulation into various delivery systems to maximize their therapeutic efficacy. One of these systems can also be crystals of nontoxic metal-organic frameworks (MOFs). In this work, we studied incorporation of a bioactive ruthenium(III) complex (RuC) inside MOFs derived from γ-cyclodextrin (γ-CD) and biocompatible potassium ions, forming CD-MOF-1. Viability studies in vitro were carried out using spheroids of human hepatoblastoma cell line HepG2. These studies revealed that the RuC-CD-MOF-1 system provides effective cancer cell suppression through slow gradual release over a longer period (>10 days) while reducing acute cytotoxic effects associated with naked RuC. This combination was defined for further development and optimization as a drug-delivery platform for metallodrugs.
Keywords: Ruthenium; viabilita buněk; protinádorové látky; Cell Proliferation; buňky Hep G2; Drug Screening Assays, Antitumor; molekulární struktura; Cyclodextrins; komplexní sloučeniny; Molecular Structure; Cell Survival; gamma-Cyclodextrins; Metal-Organic Frameworks; cyklodextriny; ruthenium; Coordination Complexes; porézní koordinační polymery; lidé; Humans; Hep G2 Cells; proliferace buněk; screeningové testy protinádorových léčiv; gama-cyklodextriny; Antineoplastic Agents